"I was already in the system from the start": how substance-using women in the street sex trade make decisions about pregnancy. (4th March 2022) - Dewey, Susan; Brown, Kyria; Hankel, Jennifer; Anasti, Theresa
Abstract: The present study examines how substance-using women in the street sex trade formulate understandings of pregnancy at the intersections of healthcare, social services, and family systems in ways that reflect internalized dominant cultural assumptions about substance use, motherhood, and the street sex trade. Three primary frameworks emerged with respect to pregnancy-related decision-making as prompted by heightened scrutiny, intensified stigma, and prioritization of fetal over maternal wellbeing. Healthcare, social services, and family systems can improve care for pregnant substance-using women in the street sex trade by acknowledging the dynamic interplay between women's substance use, relationships, and pregnancy-related decision-making as well as the intersectional harms compounded by child custody loss and persistent lack of support to low-income women.